Patent Races with Dynamic Complementarity - Andrea Blasco (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
Recent models of multi-stage R&D have shown that a system of weak intellectual property rights may lead to faster innovation by inducing firms to share intermediate technological knowledge. In this article I introduce a distinction between plain and sophisticated technological knowledge, which has not been noticed so far but plays a crucial role in determining how different appropriability rules affect the incentives to innovate. I argue that the positive effect of weak intellectual property regimes on the sharing of intermediate technological knowledge vanishes when technological knowledge is sophisticated, as is likely to be the case in many high tech industries.
Keywords: L10; O30; 330